Teachers' Strategies in Teaching Reading Comprehension in SMPN 7 Medan City - Br Bangun, Zefanya Olivia; Tarigan, Sri Ninta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Globalization has made English increasingly important as an international language in commerce, technology and education. Knowing how to speak English is certainly very useful and beneficial, given the importance of the English language. Of the four skills that teachers teach their students, reading is one of the most important skills in English and provides many benefits. This study examines the strategies used by English teachers to teach reading comprehension and their implementation at SMPN 7 Medan City. This research is descriptive qualitative in nature, using observation and interviews. Two English teachers served as informants in this study. The result of this study is based on the observation, the researcher first found that there are three strategies used by English teachers, namely (1) Scaffolding, (2) Question Answer Relationship (QAR) and (3) Discussion Strategy. Teachers use these strategies to help students understand the reading material. Students are encouraged to concentrate more on the text, and teachers can also assist students in developing the meaning of the reading material so that they can more quickly understand the content. In the Application of strategies used by English teachers to teach reading comprehension. First, scaffolding strategies that can create readable concepts are the methods used by the teacher. Second, this teacher uses the QARs strategy, where she asks her students about the terms she uses in the text after they finish reading it. Third, the discussion strategy which can make students more active in exchanging ideas when discussing with classmates. This method is used to ensure that students understand the text they read.